Annual Plan 1994-95 Introduction and General Statements Volume-1 Government of Meghalaya - Planning Commission (Planning Commission, 1994)
Area and Location : Meghalaya is one of the smallest states in India and is strategically located in the north eastern region. The total area of the state is 22,429 sq. km. The stale lies between 25° 5" east and 26° 10" north latitudes and 98° 47" and 97° 47" east longitudes. The state is a land locked territory sharing borders with Assam in the north and the east and with Bangladesh in the south and the west. The length of international boundary touching the state is 296 kms. The original composite districts of the United Khasi and Jaintia Hills and the Garo Hills have now been divided into 7 (seven) districts namely., (1) Jaintia Hills (2) East Garo Hills (3) West Khasi Hills (4) South Garo Hills (5) East Khasi Hills (6) West Khasi Hills.
Government of Meghalaya Planning Department
Government of Meghalaya Planning Department